The Wiley-Blackwell companion to cultural geography - Johnson, Nuala Christina, 1962- (Chichester, West Sussex, UK : Malden, MA : Wiley-Blackwell, 2013)
"A significantly revised new edition of this authoritative reference volume which traces the historical evolution of cultural geography through to the very latest research"--
Introduction / Nuala C. Johnson, Richard H. Schein, and Jamie Winders -- Theoretical dispatches -- Foundations -- Landscapes -- Natures/cultures -- Circulations/networks/fixities.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Human geography; SOCIAL SCIENCE / Human Geography; Human geography; Kulturgeografi; Electronic books; Electronic books; Electronic books